A comparative evaluation of human factors intervention approaches in aviation safety management - Chan, Wesley Tsz-Kin; Li, Wen-Chin (Springer, 2023)
In the Human Factors Intervention Matrix (HFIX) framework, human factors interventions are categorized into five different approaches and each of these approaches can be evaluated by five different evaluation criteria of feasibility, acceptability, cost, effectiveness, and sustainability. Although the outcome of evaluations can assist safety management practitioners in the selection of more viable safety recommendations, there exists a research gap on how the five different approaches differ with each other. In this study, overall comparisons of the five approaches in HFIX were carried out using the five evaluation criteria. Each intervention approach was also compared independently with other approaches in a pairwise manner to highlight comparative strengths. It was discovered that amongst the five evaluation criteria, only feasibility, cost, and effectiveness differed across the five approaches. Task- and human-based interventions were more feasible, whereas task- and organization-based interventions were rated more highly on cost, reflective of better cost-efficiency. Subjective differences in evaluation were also identified in effectiveness, showcasing that cognitive biases can exist within evaluative frameworks. The findings will benefit safety practitioners and managers in the selection and application of human factors intervention strategies, especially in resource constrained situations in the real world.
Keywords: Human Factors Intervention; Evaluation; Safety Management